International Trade Law and Coffee Supply Chains: Ensuring Fair Pricing and Legal Certainty in Export Markets - Ibrahim Aji; Adi Saputra; Yusfika Ely Nur Afifah; Mahfudlon Mahfudlon; Dian Wibowo; Annie Myranika (International Journal of Business and Quality Research, 2026)
International coffee trade plays a strategic role in the global economy, yet it faces complex legal challenges related to market access, regulatory divergence, and sustainability standards. This study examines the effectiveness of international trade law frameworks in governing coffee commodity exports, with particular attention to developing countries such as Indonesia. Using a qualitative approach, this research analyzes key legal instruments including World Trade Organization agreements, bilateral trade arrangements, and certification schemes such as fair trade and geographical indications. The findings reveal that while existing frameworks provide mechanisms for dispute resolution and market integration, significant gaps remain in protecting smallholder farmers and ensuring equitable value distribution. Furthermore, inconsistencies in non-tariff measures and sustainability requirements often create barriers to entry for exporters. The study proposes strengthening legal harmonization, enhancing institutional coordination, and integrating sustainability principles into binding trade regulations to support inclusive and resilient coffee trade systems globally. These reforms are essential to balance economic competitiveness with social justice and environmental protection in international coffee trade governance systems worldwide. Keywords: International Trade Law, Coffee, Supply Chain, Fair Pricing